2012
DOI: 10.1088/1009-0630/14/4/09
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density and Optical Emission Measurements of SF6/O2Plasmas for Silicon Etch Processes

Abstract: This work investigates internal plasma process parameters using a hairpin resonance probe and optical emission spectroscopy. The dependence of electron density and atomic fluorine on the percentage of oxygen in an SF6/O2 discharge was measured using these methods. An RIE Oxford Instruments 80 plus chamber was used for the experiments. Two different process powers (100 W and 300 W) at a constant pressure (100 mTorr) were used, and it was found that the optical emission intensity of the 703.7 nm and 685.6 nm lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Such variation of the F/Ar ratio is a direct consequence of the conversion of the SF 6 into other gases (SO x F y , F 2 , etc.). Similar curves of the F/Ar intensity ratio have been obtained, or can be retrieved in extensive amount of studies related to fluorine-based plasmas [45,74,78]. Simultaneously, for an O 2 percentage lower than 10%, the oxygen atom density is believed to be negligible because of recombination processes leading to SO x F y molecules.…”
Section: Etching In Sf 6 /O 2 Plasmasupporting
confidence: 74%
“…Such variation of the F/Ar ratio is a direct consequence of the conversion of the SF 6 into other gases (SO x F y , F 2 , etc.). Similar curves of the F/Ar intensity ratio have been obtained, or can be retrieved in extensive amount of studies related to fluorine-based plasmas [45,74,78]. Simultaneously, for an O 2 percentage lower than 10%, the oxygen atom density is believed to be negligible because of recombination processes leading to SO x F y molecules.…”
Section: Etching In Sf 6 /O 2 Plasmasupporting
confidence: 74%
“…For our process, this means that, during removal of the 25 nm thick silicon adhesion layer, less than 2 nm of the HSQ mask, which in our case is several hundreds of nanometer thick, will be lost. This result corresponds well to similar plasmas obtained in different systems showing highly selective silicon etching while conserving SiO2 (in our case HSQ) [28]. We furthermore observed no or minor etching of SCD during the SF 6 pulse and no roughening of the exposed SCD surface.…”
Section: Selective Icp-rie Of Adhesion Layer and Scd Structuringsupporting
confidence: 91%
“…Another reason for the reduction of F could be due to the resonance enhanced quenching of the Argon transition 750 nm which is correlated to the electron density. Morshed et al [53] found that the electron density decreases with increased O2 dissociation rate (above O2=30%) in the plasma. Argon provides stability and enhances anisotropic etching and it decreases with decrease in the electron density in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Morshed et al experimentally investigated that electron density increases with applied power and is correlated to the concentration of fluorine [53], [63]. The increase in power increases the electron density and hence increases the F density due to the electron collision with the SF6 gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation